(untitled) - Goddard, Elizabeth (Center Point Large Print, 2022)
"Former FBI Special Agent Jack Tanner is working as a detective in Montana when he comes across a body in the national forest during a search and rescue mission. Hes committed to finding the killer, even if it means working alongside his old flame, US Forest Service Special Agent Terra Connors. When Terra discovers that the murder victim had ties to a powerful and dangerous trafficker of archaeological artifacts, the investigation takes a deadly turn - one that hits too close to home. As Terra fears she lacks the courage to face what comes next, Jack is more determined than ever to protect her. But hes failed her before. If he fails this time, it will cost them far more than just their hearts."--
Keywords: Fiction; Fiction; Montana; Investigation; Murder; Fiction; Forest reserves; Search and rescue operations; Archaeological thefts; Fiction; Man-woman relationships; Fiction; Family secrets; Fiction; United States; Intelligence officers; Fiction; Romantic suspense fiction; Detective and mystery fiction; Romance fiction; Thrillers (Fiction); Christian fiction